IMPORTANT AERODYNAMIC PARAMETERS OF FLAPPING-WING UNMANNED AERIAL VEHICLES - Razak N.A.; Abas A.; Itam Z. (Nova Science Publishers, Inc., 2023)
Unmanned aerial vehicles (UAVs) with flapping wings have been the focus of many recent studies due to their numerous applications. This chapter emphasises the essential parameters for the development and evaluation of flapping-wing UAVs. These parameters should be considered to successfully design flapping-wing UAVs. This chapter provides a short description of several topics related to flapping-wing flight and covers the basics of unsteady aerodynamic force generation.Subsequently, this chapter discusses important parameters of flappingwing aerial vehicles, such as Reynolds number, flow unsteadiness, wing geometry and flapping kinematics. This chapter also presents the modelling of flapping wing aerodynamics using quasi-steady approaches. 2019 Nova Science Publishers, Inc.